Influence of Intestinal Indigenous Microbiota on Intrafamilial Infection by Helicobacter pylori in Japan - Osaki, Takako; Zaman, Cynthia; Yonezawa, Hideo; Lin, Yingsong; Okuda, Masumi; Nozaki, Eriko; Hojo, Fuhito; Kurata, Satoshi; Hanawa, Tomoko; Kikuchi, Shogo; Kamiya, Shigeru (Frontiers in Immunology, 2018)
Helicobacter pylori is a causative pathogen of chronic gastritis, gastric ulcer disease and gastric cancer. Humans are known to be a natural host for H. pylori, and tend to acquire the pathogen before the age of 5 years. The infection may then persist lifelong if eradication therapy is not applied. One of the modes of transmission of H. pylori is between family members and therefore the presence of infected family members is an important risk factor in children. However, other environmental factors have not been fully analyzed. The present study was performed to clarify whether and to what extent intestinal microbiota affect H. pylori intrafamilial infection. The fecal specimens from H. pylori-infected infants and H. pylori-infected and non-infected family members were collected in cohort studies conducted by Sasayama City, Hyogo Prefecture from 2010 to 2013. In total, 18 fecal DNA from 5 families were analysed. Samples were amplified using 16S rRNA universal primers and the amplicons were sequenced using the Ion PGM system. PCoA analysis demonstrated that there was no difference in intestinal microbiota between H. pylori-positive and H. pylori-negative groups. In intrafamilial comparison tests, the Manhattan distance of intestinal microbiota between the H. pylori-infected infant proband and H. pylori-negative mother was nearest in the family with low intestinal microbial diversity. However, in the family with the highest intestinal microbial diversity, the nearest Manhattan distance was shown between the H. pylori-infected infant proband and H. pylori-infected mother. The results in this study showed that the composition of the intestinal microbiota was very similar between members of the same family and as such, colonization with organisms highly similar to the infected parent(s) may be a risk factor for H. pylori infection in children.